Heart Sound Detection Using an Ultra-Wideband FMCW Radar - Wenzel, Marvin; Tegowski, Bartosz; Albrecht, Nils C.; Langer, Dominik; Koelpin, Alexander (IEEE MTT-S International Microwave Symposium Digest, 2023)
This paper investigates the detection of vital signs with an ultra-wideband frequency modulated continuous wave (FMCW) radar. In addition to respiration and pulse wave signals, the heart sound signal is retrieved, which has so far only been achieved with CW radars. Proof-of-concept measurements were performed with a subject seated 0.5 m away from the radar. With respect to a reference electrocardiography (ECG), a high accuracy of 95.7% was achieved for the instantaneous beat-to-beat heart rate.
Created from Fastlane, Scopus look-up
Keywords: FMCW radar; heart sound detection; ultra-wideband radar; vital sign detection